2021
DOI: 10.1515/jpem-2021-0403
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and phenotypic spectrum of vitamin D dependent rickets type 1A: our experience and systematic review

Abstract: Background Vitamin D dependent rickets type 1 (VDDR1) is a rare disease due to pathogenic variants in 1-α hydroxylase gene. We describe our experience with systematic review of world literature to describe phenotype and genotype. Methods Seven patients from six unrelated families with genetically proven VDDR1 from our cohort and 165 probands from systematic review were analyzed retrospectively. The clinical features, biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Of the 7 patients, 4 had episodes of hypocalcemic seizure. In 165 patients, seizures and motor-deformity were more common during infancy(11 of 31 infants) and post-infancy, respectively (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 7 patients, 4 had episodes of hypocalcemic seizure. In 165 patients, seizures and motor-deformity were more common during infancy(11 of 31 infants) and post-infancy, respectively (38).…”
Section: Discussionmentioning
confidence: 99%
“…At the onset of radiographic changes, the calcitriol dose modified to 0.25-0.5 μg / day. They concluded that physiological doses of calcitriol (0.25-0.75 μg / day) could improve the clinical and laboratory profile of patients (38). Dhull et al considered doses of 30 ng/kg/day and 2 mmols/kg/day for calcitriol and phosphate, respectively, for both patients.…”
Section: Discussionmentioning
confidence: 99%
“…As seen in 25-hydroxylase deficiency, the elevation of serum ALP levels is also typical of 1-alpha-hydroxylase deficiency (also defined as vitamin D-dependent rickets type 1 or VDDR1), a somewhat more common condition in which the genetic defect causes a defective conversion of 25OHD into the active form of vitamin D. In the case series published by Dodamani et al. ( 22 ), in which the authors reviewed the clinical features of a total of 165 probands affected by VDDR1 found in literature, the patients presented with markedly elevated ALP levels (on average 1480 IU/L). Ozden et al.…”
Section: The Role Of Alp In the Diagnosis Of Calcipenic Ricketsmentioning
confidence: 99%
“…Some drugs such as antiepileptics and glucocorticoids may disrupt vitamin D metabolism and, in some cases, also cause decreased calcium absorption and increased renal losses, contributing to hypomineralization. The rare genetically determined disorders vitamin D-dependent rickets (VDDR) types 1A and 1B, caused by mutation in genes encoding cytochrome P450 family 27 subfamily B member 1, i.e., 1alpha-hydroxylase (CYP27B1) or cytochrome P450 Family 2 Subfamily R Member 1, i.e., 25-hydroxylase (CYP2R1), are included in the vitamin D-dependent forms of altered mineralization since they are cured with specific analogs of vitamin D, such as 1alpha-hydroxylated forms of vitamin D or 25-hydroxylated vitamin D, respectively [ 1 , 12 ].…”
Section: Physiopathology Of Defective Mineralization and Proposed Pat...mentioning
confidence: 99%